2013
DOI: 10.1016/j.apergo.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socio-cultural background and product value in usability testing

Abstract: This article examines the influence of socio-cultural background and product value on different outcomes of usability tests. A study was conducted in two different socio-cultural regions, Switzerland and East Germany, which differed in a number of aspects (e.g. economic power, price sensitivity and culture). Product value (high vs. low) was varied by manipulating the price of the product. Sixty-four test participants were asked to carry out five typical user tasks in the context of coffee machine usage, measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…the brand of a cell phone [11,35]), that is, product features that are unrelated to usability may have an influence on usability variables (e.g. aesthetic design features, price, product value, and life style associated with a product [45]). This may suggest a higher significance of such factors in the leisure domain than at work, where efficiency and performance appear to play a dominant role.…”
Section: Usage Domainmentioning
confidence: 99%
“…the brand of a cell phone [11,35]), that is, product features that are unrelated to usability may have an influence on usability variables (e.g. aesthetic design features, price, product value, and life style associated with a product [45]). This may suggest a higher significance of such factors in the leisure domain than at work, where efficiency and performance appear to play a dominant role.…”
Section: Usage Domainmentioning
confidence: 99%
“…Menurut [8] Orang-orang dari budaya yang berbeda berpikir dan berperilaku berbeda, dan perbedaan-perbedaan ini akan mempengaruhi bagaimana mereka memahami, mengembangkan, dan menggunakan komputer. Dari beberapa literatur yang lain didapatkan hasil penelitian bahwa latar pengguna berpengaruh pada tingkat usability [9][10] [11] [12] [13]. Pada penelitian ini, peneliti menggunakan variabel latar pengguna berupa gender, angkatan masuk PT, dan frekuensi penggunaan LMS.…”
Section: Pendahuluanunclassified
“…Terakhir adalah penelitian [13] mengkaji pengaruh latar belakang sosial budaya dan nilai produk pada hasil tes kegunaan yang berbeda. Sebuah studi dilakukan di dua wilayah sosial budaya yang berbeda yaitu Swiss dan Jerman Timur dimana keduanya memiliki perbedaan dalam beberapa aspek (misalnya kekuatan ekonomi, sensitivitas harga, dan budaya).…”
Section: Pengaruh Latar Belakang Pengguna Terhadap Tingkat Usabilityunclassified
“…Cultural background of test participants e.g. has been shown to influence the outcomes of usability tests of a consumer product with a high or low product value [27]. It has also been shown that the results of usability tests may depend on the setup of the usability laboratory (e.g.…”
Section: Influencing Factors In Usability Tests -The Four Factor Frammentioning
confidence: 99%